Effect of in-package cold plasma treatments on the quality of minimally processed apples - Denoya, Gabriela Inés (2023)
Cold plasma technology is being increasingly used for food preservation and, incipiently, for minimal processing of fruit. Therefore, the objective of this work was to study the effect of in-package cold plasma (generated in atmospheric-pressure air by a low-frequency −50 Hz-dielectric barrier discharge operating at 30 kV) on the quality of minimally processed apples during refrigerated storage. Apple slices were subjected to the different treatments following a completely randomised design with a 3 × 3 factorial arrangement. The independent variables were the exposure time (0, 1 and 3 min) and the storage times (1, 4 and 7 days). Cold plasma treatments preserved the quality of the fruit, maintaining the tissue structure. Plasma treatment applied for 1 min rendered apple slices with the highest antioxidant content but only at day 1. Even though polyphenoloxidase activity was reduced by the treatment, it was not sufficient to stabilise the antioxidant content during storage.